A comparative examination of the health status of earthquake-affected and non-earthquake-affected adolescents in Yushu - Zhao, Fangjie; Tang, Bihan; Yang, Hongyang; Wu, Jing; Chen, Qi; Zhang, Lulu; Liu, Xu (Frontiers in Public Health, 2022)
Background Yushu, Qinghai province is located in remote Tibetan plateau in Western China, struck by a disastrous earthquake in 2010. Methods The study aimed to compare health status of adolescents who had (Exp-Group) and had not (Non-Group) experienced Yushu earthquake, 7 years after it occurred; additionally, group-specific predictors of health status were identified. A cross-sectional research was adopted among students from two junior schools in Yushu, whereby two groups were compared. Descriptive statistics, t-tests, Wilcoxon rank-sum tests, Kruskal-Wallis H tests, stepwise linear regression were used to analyze data. Results Exp-Group scored higher than Non-Group on Physiological Component Summary (PCS) but not Mental Component Summary (MCS). Among Exp-Group participants, lower PCS scores were predicted by "house damaged", "injured", "family member injured", "family member or friend dead". Lower MCS scores were predicted by "family member or friend dead". Among Non-Group participants, PCS scores were predicted "residence", "family member or friend dead". Lower MCS scores were predicted by "not living with parents". Conclusion Lower PCS and MCS scores of Exp-Group adolescents are mainly contributed to earthquake-related injuries, while lower PCS and MCS scores of Non-Group are related to poor living conditions and fact of left-behind child.